Future prospects for smallhold native chicken producers in the Philippines - Lambio, Angel L. (Elpidio Quirino Professional chair lecture, 2005)
The Philippine native chickens are believed to have originated from the domesticated red jungle fowl. Through natural selection, genetic isolation and mating with exotic stocks, they have evolved into a population of mixed genetic group which exhibit variability in many qualitative and quantitative traits. As of 2004, the total chicken population in the country was estimated to be 129.43M head. Of this number, the proportion of the native type was 56.16%. The Philippine native chickens has remained an important source of protein food and extra income for the rural farmers in spite of the growing popularity of chicken products from exotic commercial hybrids. Many rural farmers prefer to raise this native type of chickens because they require very minimal production inputs. These chickens are noted for their hardiness and resistance and have the ability to survive and reproduce even under the most marginal of environmental and management conditions. Besides, their meat and eggs are preferred by customers over that coming from commercial hybrid chickens because of their unique quality attributes particularly of meat suited for cooking traditional Filipino dishes. The intense yellow pigmentation of their skin and egg yolk are other qualities which are desired by many consumers. These products can very well considered as organically produced.The expansion of the native chicken industry is relatively slow as reflected in the very slow population growth rate. Native chicken producers are smallholder farmers which have very limited financial resources to warrant providing appropriate management to his flock.On the other hand, the growing popularity of organic food, the active movement for humane treatment of animals, the dependence on imported input to production of the commercial hybrids, and the recent outbreak of the avian influenza(bird flu) in many countries, provide a very good opportunity for smallhold native chicken producers to intensify the production and marketing of the products of native type of chickens.